Kajian Fenomenologi Tektonika Rumah Batak Toba - Widriyakara Setiadi; LMF Purwanto; Antonius Ardiyanto; Rudiyanto Soesilo; B.Tyas Susanti (Universitas Islam Negeri Sunan Ampel Surabaya, 2022)
Indonesia is a super cultural power country, rich in customs and culture line from Sabang to Merauke, from Nias to Rote Island. Cultural wealth breeds architectural diversity. The potential of original Indonesian architecture has begun to be left behind and eroded by foreign cultures. The postmodern era has raised Nusantara Architecture to the world stage. Researches on the wealth of Nusantara architecture begin to bloom like mushrooms in the rainy season. The phenomenon of the skills or expertise of the masters has made traditional houses an endless research material. The purpose of this research is to explore the treasures of the Indonesian nation's wealth, especially the craftsmanship skills of Indonesian ancestors. The phenomenon of tying, knitting, and stringing materials into architectural masterpieces is a uniqueness and uniqueness that other nations do not have. The method used in this study uses the phenomenological method. Where in the vernacular architectural phenomenology is divided into two branches; first: related to space, place, and atmosphere, second: related to tectonic or the art of construction more on the elements of craftsmanship. The results of this study reveal that simple and straightforward technology becomes effective when it comes to craftsmen who have special skills. The conclusions of this study indicate that the skill of the masons is more dominant than the tools used, on the other hand, currently tools are more dominant than the skills of the masons.